2007
DOI: 10.2108/zsj.24.360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships and Reproductive-isolation Mechanisms among the Fejervarya limnocharis Complex from Indonesia (Java) and Other Asian Countries

Abstract: In order to elucidate the genetic relationships and reproductive-isolation mechanisms among the Fejervarya limnocharis complex from Indonesia and other Asian countries, allozyme analyses and crossing experiments were carried out using 208 individuals from 21 localities in eight Asian countries. The allozyme analyses revealed that 17 enzymes examined were controlled by genes at 27 loci, and that 7.9 phenotypes were produced by 5.2 alleles on average. The two species recognized in F. limnocharis sensu lato from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
(29 reference statements)
4
22
0
Order By: Relevance
“…Several researchers (Kosuch et al, 2001;Kurabayashi et al, 2005;Frost et al, 2006;Sumida et al, 2007;Kotaki et al, 2010;Hasan et al, 2012a) have argued that members of the genus Fejervarya could be separated into 2 distinct groups-Southeast and South Asian-based on molecular data. This view was further supported by researchers who clearly showed complete hybrid inviability between these 2 groups by crossing experiments Djong et al, 2007;Islam et al, 2008b). In this study, we found that the divergence value of these 2 groups is considerably high (16S diversity = 11.8%), which is in keeping with the previous studies mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…Several researchers (Kosuch et al, 2001;Kurabayashi et al, 2005;Frost et al, 2006;Sumida et al, 2007;Kotaki et al, 2010;Hasan et al, 2012a) have argued that members of the genus Fejervarya could be separated into 2 distinct groups-Southeast and South Asian-based on molecular data. This view was further supported by researchers who clearly showed complete hybrid inviability between these 2 groups by crossing experiments Djong et al, 2007;Islam et al, 2008b). In this study, we found that the divergence value of these 2 groups is considerably high (16S diversity = 11.8%), which is in keeping with the previous studies mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…The diversity of evolutionary processes affecting character divergence, which may lead, for example, to striking cases of morphological crypsis or to situations where a single species may exhibit extraordinary levels of inter‐ or even intrapopulational polymorphism, call for the use of multiple lines of evidence to assess the status of species and to discover new ones (e.g. Djong et al. 2007; Brown & Twomey 2009; Vences et al.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there are now regarded to be 32 species for the genus Fejervarya . Thus, the F. limnocharis group to be identified should be called the Fejervarya limnocharis complex (Djong et al, 2007). Furthermore, there are few morphological differences and few morphological characteristics usable for classification throughout this genus, not only for the F. limnocharis complex, and so it is difficult to correctly identify species.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses using allozymes and mitochondrial DNA have been carried out for several populations of the F. limnocharis complex in Thailand (Sumida et al, 2007;Djong et al, 2007). Both allozyme and mtDNA analyses revealed that the Bangkok population differed greatly from those of F. limnocharis from the type locality, Java, Indonesia.…”
Section: Introductionmentioning
confidence: 99%